Pengaruh Video Tutorial PJOK Terhadap Hasil Belajar Pjok di SMPN 1 Payakumbuh - Fahrul Hadi; Gusnita Darmawati; Firdaus Annas; Yulifda Elin Yuspita (Ikatan Dai Indonesia, 2025)
This research was conducted in the odd semester of 2023/2024, where the author collected student data and grades. The data were then processed and analyzed to determine the impact of video tutorials on student learning outcomes in Physical Education (PJOK). The required data collection took place in July 2023, and the study was conducted in both the experimental and control classes to assess the impact on learning outcomes. The average cognitive learning outcomes obtained through the post-test between the control and experimental classes can be used to determine the extent of the differences in learning outcomes in PJOK between students taught through video tutorials and those not taught through video tutorials.